2017
DOI: 10.4171/jncg/268
|View full text |Cite
|
Sign up to set email alerts
|

Braided quantum SU(2) groups

Abstract: We construct a family of q-deformations of SU(2) for complex parameters q = 0. For real q, the deformation coincides with Woronowicz' compact quantum SUq(2) group. For q / ∈ R, SUq (2) is only a braided compact quantum group with respect to a certain tensor product functor for C * -algebras with an action of the circle group.2010 Mathematics Subject Classification . 81R50 (46L55, 46L06). Key words and phrases. braided compact quantum group; SUq(2); Uq(2). S. Roy was supported by a Fields-Ontario Postdoctoral f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 11 publications
3
43
0
Order By: Relevance
“…the corresponding C˚-algebras are isomorphic. This was proved already in [23,Appendix A.2] for real q, then stated in [3, Section 3.1] and proved in [5,Section 2]. Similarly Podleś spheres are all isomorphic to a certain extension K ' K by CpTq, where K is the algebra of compact operators on a separable Hilbert space ( [19], see also [13,Proposition 4]) or to the minimal unitization of K (the standard quantum sphere).…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…the corresponding C˚-algebras are isomorphic. This was proved already in [23,Appendix A.2] for real q, then stated in [3, Section 3.1] and proved in [5,Section 2]. Similarly Podleś spheres are all isomorphic to a certain extension K ' K by CpTq, where K is the algebra of compact operators on a separable Hilbert space ( [19], see also [13,Proposition 4]) or to the minimal unitization of K (the standard quantum sphere).…”
Section: Introductionmentioning
confidence: 55%
“…Section 3 recalls the details of the braided version of SUp2q and in Section 4 we study the quotient sphere S 2 q " SU q p2q{T. Section 5 is devoted to the definition and study of the three-dimensional irreducible representation of SU q p2q found as an irreducible subrepresentation of the tensor square of the fundamental representation (cf. [5,Section 5]) and in Section 6 we find the commutation relations implied by existence of an action of the braided quantum group SU q p2q satisfying certain conditions suggested by the quotient construction from Section 4 (cf. Section 5.5).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations